GENRE FEATURES OF NOVEL «KRYVAVOOKI HEAD» BY PETER SOSENKO - Вівчарик, Н. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article analyzes the socio-psychological novel Peter Sosenko «Kryvavooki head». A typological analysis of novel Mykhailo Kotsiubynskyi «Persona grata». After images of the main characters revealed the psychology of the character assassin. For this purpose consideration involved dreams, childhood memories that emerge in the minds of the characters. Proved that the stream of consciousness indicates hesitation, doubt, internal conflicts, which ripen in the souls of heroes. Simultaneously, a detailed analysis of national and patriotic issues novels Peter Sosenko.